Body composition analysis components as markers for coronary artery diseases in type 2 diabetic patients - Pritika S. Dutta, M.Sc; Vineetha K. Ramdas Nayak, MD; Dhiren Punja, MD (Journal of Taibah University Medical Sciences, 2022)
الملخص: أهداف البحث: الهدف من الدراسة هو دراسة قدرة مكونات تحليل تكوين الجسم على التنبؤ بمرض الشريان التاجي لدى السكان الهنود الآسيويين المصابين بالسكري من النوع الثاني. طرق البحث: تم إجراء دراسة الحالات والشواهد هذه بمشاركة 50 شخصا من مرضى السكري النوع الثاني المصابين بمرض الشريان التاجي في مجموعة التجربة مع 50 شخصا أخرين من مرضى السكري النوع الثاني كمجموعة تحكم أعمارهم بين 40-70 عاما من السكان الهنود الآسيويين من زائري قسم أمراض القلب في أحد مراكز الرعاية الصحية المتقدمة في مدينة مانيبال بالهند. تم تأكيد تشخيص مرض الشريان التاجي عن طريق اختبارات تخطيط كهربية القلب والتغيرات في تصوير الأوعية التاجية. تم تقييم القياسات الجسمانية. كما تم تحليل مكونات الجسم باستخدام جهاز بوديستات 1500 ام دي دي. النتائج: أدت زيادة الدهون بمقدار وحدة واحدة إلى ازدياد احتمالات الإصابة بأمراض الشريان التاجي بمقدار 4.434 مرة لدى مرضى السكري من النوع الثاني. وأدى انخفاض الكتلة العضلية بمقدار وحدة واحدة إلى ازدياد احتمالات الإصابة بأمراض الشريان التاجي بمقدار 4.976 مرة. كما أدت زيادة مؤشر كتلة الدهون في الجسم بمقدار وحدة واحدة إلى ازدياد احتمال الإصابة بأمراض الشريان التاجي بمقدار 1.747 مرة. الاستنتاجات: تعتبر زيادة كتلة الدهون وانخفاض الكتلة العضلية في الجسم من العلامات المهمة للتنبؤ بمرض الشريان التاجي بين مرضى السكري من النوع الثاني. Abstract: Objectives: The objective of the current study is to investigate the potential of body composition analysis components for predicting coronary artery disease (CAD) in the Type 2 diabetic Asian Indian population. Methods: This case–control study was performed by recruiting 50 type 2 diabetic patients with CAD along with 50 controls. The participants recruited were those between the ages of 40–70 who visited the Department of Cardiology at a tertiary care referral centre in Manipal, India. The diagnosis of CAD was confirmed by electrocardiogram tests and coronary angiogram changes. An anthropometric evaluation was conducted, and body composition analysis was conducted using Bodystat 1500MDD equipment. Results: In type 2 diabetics, for a unit increase in fat, the odds of CAD increased by 4.43 times. For a unit decrease in lean mass, the odds of CAD increased by 4.98 times. For a unit rise in body fat mass index, the odds of CAD increased by 1.75 times. Conclusion: In Type 2 diabetics, increased body fat mass with decreased lean tissue mass were valuable markers of CAD. Future studies can examine the benefits of different types of nutritional and exercise interventions targeted at improving muscle mass and reducing fat content in the body with an aim to reduce the occurrence of CAD in patients diagnosed with T2DM.